Gerakan Pemurnian Islam Syekh Muhammad Arsyad Al-Banjari di Kalimantan Selatan - Arianti, Anita (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2017)
Syekh Muhammad Arsyad al-Banjari’s purification movement in South Kalimantan identified four fields of thought, ie. theology (aqidah), Islamic law (syari’ah), preaching (dakwah) and Sufism (tasawuf). In the theology, Syekh Arsyad purified Islam from animism ritual which is called bid’ah dhalalh (unlawful tradition). His purification method is explained clearly in his Tuhfah al-Ragibin, particularly in criticism of ‘Menyanggar Banua’ (a ritual for village safety) and ‘membuang pasilih’ (a ritual for breaking unlucky streak). Syekh Arsyad declared that both rituals which are often performed by ‘sesajen’ (a scarified food) is bid’ah dhalalah, consequently the performer becomes definitely unbeliever (kafir). In the syari’ah, Syekh Arsyad focused detailly his attention on cleanliness (thaharah) as well as poor due (zakat). In his Sabil al-Muhtadin li al-Tafaqquh fi Amr al-Din, he explained in a different perspective how to performance cleanliness and how to paying zakat of a modern agriculture. In the preaching, Syekh Arsyad formulated the method of preaching in three, dakwah bi al-hal (by doing), dakwah bi al-lisan (by verbal communication), and dakwah bi al-kitabah (by writing), the last one was a new method formulated by Syekh Arsyad. In Sufism, Syekh Arsyad followed the way of Tarekat Sammaniah in zikir and meditation. It could be understood in his both Risalah Fath al-Rahman and Risalah Kanz al-Ma’rifah.